The harmony of nature in Ahmad Tohari's thoughts through the novel Di Kaki Bukit Cibalak - Khasanah, Venus; Anoegrajekti, Novi; Setiadi, Samsi (Universitas Mulawarman, 2024)
Awareness of the importance of natural harmony as an ecosystem for human life has become an important topic to study. The phenomenon of natural damage triggers this condition due to the actions of unscrupulous people in the community. Forest clearing for industrial purposes is one of the triggers. Apart from that, the increasingly complicated management of plastic waste due to a lack of public education about this impact also triggers the destruction of natural balance. Therefore, through this article, the researcher attempts to link this paradigm with the message conveyed through the novel Di Kaki Bukit Cibalak (after this DKBC) by Ahmad Tohari. The method used in preparing this article is genetic structuralism with a literary sociology approach. The results of the research show that based on the story structure found, the author's worldview about the importance of maintaining natural harmony is embedded in the story being told. This view also shows that the harmonization and harmony of nature is an important foundation for Indonesia's golden generation. Therefore, the author's worldview can be an important pillar as an alternative environmental education material delivered through school education.